Preliminary Analysis on the Status Quo and Problems of Land Use of Educational Space in Primary and Secondary Schools in the Downtown Area, Tianjin- Results of data analysis based on information entropy and equilibrium. (September 2019) - Zhang, Shouren; Ye, Qing; Du, Yawei; Song, Kun
Abstract: In this article, in order to have a better understanding of the current situation and supply-demand challenges with regard to the land use of educational space in primary and secondary schools in the downtown area, Tianjin and address the related problems, the comparative analysis is conducted on the land-use layout of 30 ordinary primary and secondary schools. In addition, for these primary and secondary schools, based on the information entropy, balance and dominance of land-use structure, and in conjunction with the actual conditions, spatial location and time of construction, efforts are made to analyze the diversity and balance of educational space. Generally speaking, the land-use layout of the surveyed schools falls into three types: ring-shaped with a center, linear, and group-based. Besides, thus, the main factors which exert certain influence on the pattern of spatial layout and the land-use structure of educational space in primary and secondary schools in the downtown area, Tianjin are identified by data analysis. It provides reference for the intensive use of educational space in primary and secondary schools, and lays a solid foundation for formulating a series of land-use planning and management policies targeted at primary and secondary schools.